THE ROLE OF THE PROCESSING INDUSTRY SECTOR IN REGIONAL ECONOMIC GROWTH (IN DUMAI CITY) - Lanjar Sumarno; Chronika Sari; Soharto Ngudiwaluyo; Armis Armis (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2022)
The purpose of this study is to determine the role of the processing industry sector in regional economic growth (in Dumai City). It can be concluded from the calculation results that the processing industry sector has a very large positive impact on the Gross Regional Domestic Product (GRDP) Prod uk in Dumai City, with an average of 54.82%. The manufacturing industry sector has increased every year from the 2010-2018 period. Thus, the role of the processing industry sector in the economic growthin Dumai City has a very positive impact and can increase the Gross Regional Domestic Product (GRDP) of the processing industry sector.